ADDITIVE-FREE Cu ELECTRODEPOSITION
By applying appropriate current density and conditions in the copper electrolytic deposition cell, electrolytic deposit of copper from acidic aqueous solutions containing Ni and Co solves the problem of forming incoherent copper deposits without the use of additives, achieving coherent and uniform copper deposition, reducing the risk of short circuit and subsequent processing complexity.
Patent Information
- Application Number
- CN202380065958.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-10-14
- Filing Date
- 2023-10-04
- Publication Date
- 2025-04-11
AI Technical Summary
In the prior art, when removing copper from raw materials and intermediates containing cobalt and nickel, it is difficult to form coherent and uniform copper deposits without using additives. Especially at low current density and low copper concentration, dendrites or nodules are easily formed, resulting in incoherent and easy decomposition of deposits.
Copper was electrolytic deposited from an acidic aqueous solution containing Ni and Co by applying a current density of 100 A/m2 to 210 A/m2 in the copper electrolytic deposition cell, and the temperature of the electrolytic solution was controlled from 50°C to 70°C without using organic additives.
Without the use of additives, a coherent and uniform copper deposit is successfully formed, reducing the formation of dendrites or nodules, ensuring the continuity and difficulty in decomposition of the deposits, reducing the risk of short circuits, and simplifying the subsequent processing process.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
[0001] Many cobalt- and nickel-containing raw materials and intermediates also contain a certain amount of copper, which ends up in the leach solution after dissolution of these materials. Examples are, inter alia, mattes from primary smelting of ores, intermediate hydroxide and sulphide products from Cu, Co and Ni mining, certain metallic deep-sea nodules containing Co, Ni and Mn, white alloys produced during smelting of Co and Ni products, and waste and production wastes produced during the production or use of lithium-ion or nickel metal hydride batteries.
[0002] In particular, the amount of lithium-ion batteries or their waste is expected to grow greatly, mainly due to the ongoing global electrification of the automotive industry. Lithium-ion batteries or their waste include new or discarded lithium-ion batteries, used or end-of-life batteries, production waste or battery waste, battery components such as electrode foils, electrolytes, separators, casing materials and electrode materials, or pre-processed battery materials, resulting in very complex waste streams. The key metals in such waste streams are usually copper, nickel and cobalt.
[0003] Therefore, the separation or removal of copper from aqueous solutions containing cobalt, nickel and other metals is a common hydrometallurgical operation.
[0004] WO2019121086 describes the removal of Cu based on selective precipitation by displacement deposition with a reducing agent. The Cu in such a method is precipitated in its metallic form. This is usually applied when the quality and value of the Cu product are not important. In such an operation based on displacement deposition, a Cu-containing solution is contacted with a reducing agent. The effect is to convert the soluble Cu 2+ or Cu 1+ The ions are reduced to insoluble elemental copper which then precipitates as solid metal.
[0005] Another option for removing copper is electrolytic deposition (EW), but this requires more investment than replacement deposition. In addition, the process conditions need to be adjusted.
[0006] CG Anderson (Book chapter: Optimization of Industrial Copper Electrowinning Solutions. In: Prime Archives in Chemical Engineering. Hyderabad, India, Vide Leaf, 2019) describes the electrolytic deposition of Cu directly from industrial solutions containing Cu and Ni ("direct electrowinning"), where the cathode is immersed in the solution. By applying an electric current, Cu is deposited on the cathode, separating it from other elements in the solution (such as Co, Ni, Fe or Mn). The robustness of direct electrowinning is limited and is therefore usually only applied to systems that favor good Cu deposition, such as when working at high Cu concentrations.
[0007] In other cases, electrowinning is combined with solvent extraction ("SX-electrowinning"). This combination makes Cu-EW more robust, i.e. more tolerant to process variations, and much more costly in terms of industrial installations. Examples are found in Cheng et al. (Recovery of nickel and cobalt from leach solutions by solvent extraction: Process overview, recent research and development; Proceedings of ISEC 2005). In such schemes, Cu is first extracted from an impure feed solution by solvent extraction (SX), which is generally highly selective for Cu. The extracted Cu ions are then transferred to a separate secondary Cu solution from which copper is harvested in a subsequent electrowinning operation that is not limited by elements such as Co, Ni, Mn and especially Fe present in the primary solution.
[0008] In conventional copper electrolytic deposition ("Cu-EW"), a dense and smooth Cu deposit of high chemical quality is produced. The process is typically carried out at a Cu concentration of about 35 g / L Cu to 55 g / L Cu, a H2SO4 concentration of about 160 g / L to 190 g / L, a temperature of 44°C to 56°C, and a flow rate of 200 A / m 2 Up to 450A / m 2The results are shown in Table 1. The results are shown in Table 2. The results are shown in Table 3. The results are shown in Table 4. The results are shown in Table 5. The results are shown in Table 6. The results are shown in Table 7. The results are shown in Table 8. The results are shown in Table 9. The results are shown in Table 10. Permanent cathodes comprising 316L stainless steel are mainly used, from which Cu deposits are removed via stripping (TG Robinson et al.; Copper Electrowinning: 2013 World Tankhouse Operating Data, Proceedings of Copper 2013, Santiago, Chile, 2013).
[0009] In both direct EW and SX-EW, the Cu in the electrolyte is replenished in the process, for example by feeding a Cu-rich leaching solution to the EW circuit or by returning electrolyte from the EW operation to the stripping stage of the Cu-SX process. Thus, the Cu concentration is kept high throughout the process and even concentration variations at the inlet and outlet of the EW cell are limited.
[0010] Alternatively, EW can also be applied, and its purpose is to exhaust the Cu content in the Cu-containing solution. A series of electrolytic deposition cells are placed in cascade, and each cell operates under a reduced Cu concentration, rather than replenishing the Cu concentration as described above (BC Wesstrom and O.Araujo, Optimizing Cascading Liberator, Hydrometallurgy and Electrometallurgy Metal Extraction Technology and Material Characterization Conference Paper, 151 pages, 2012 (Optimizing a Cascading Liberator, TT Chen Honorary Symp. Hydrometall., Electrometall. Mater. Charact. Proc., 151, 2012)). In this case, the main purpose is to remove Cu from the stream, rather than to produce a pure and valuable Cu product. The term used for this is "depleted Cu-EW". The physical quality of the deposited Cu is usually very poor, especially at a lower Cu concentration, so further refining is required. The reduced Cu concentration results in a very porous, incoherent sediment that can be easily decomposed. Thus, most of the sediment usually detaches from the cathode and is collected as cathode sludge at the bottom of the EW cell (Shijie Wang, Recovering copper using a combination of electrolytic cells, JOM, 54, 51-54, 2002).
[0011] Depleted Cu-EW is usually embedded in a larger hydrometallurgical process scheme, where downstream operations can only tolerate limited incoming Cu concentrations. A typical application is to recover Cu from a effluent stream, where impurities are removed from the main loop in conventional Cu electrorefining and EW operations. Typically, the acid concentration in such a process scheme is also quite high, such as 350 g / L to 400 g / L (A. Siegmund, S. Gadia, G. Leuprecht, P. Stantke, Proceedings of Copper 2013, pp. 275-283). Cu electrorefining requires electrochemical dissolution of copper from an impure anode into an electrolyte and electrochemical plating of pure copper from the electrolyte onto a cathode.
[0012] Other flowsheets dedicated to battery recycling may also involve a consumable Cu-EW step. WO19102765 describes a method in which an alloy containing Cu, Ni and Co is used as an anode in an electrolytic purification method. In this method, Cu, Ni and Co are dissolved into an electrolyte and then Cu is deposited onto the cathode. In one example, the Cu-EW step is performed by applying 1500A / m 2 The Cu concentration was reduced from 10 g / L to 1 g / L in an intermittent process at very high current densities, resulting in a Cu product with a chemical purity of 99.9%. However, the physical properties of the Cu deposits were not described. At these high current densities, Cu powders were generally produced rather than dense deposits.
[0013] The physical quality of the Cu deposit is mainly defined by the compactness of the cathode flakes (absence of pores, cracks and voids) and the smoothness of their surface (absence of dendrites, nodules and other protrusions).
[0014] A common way to alleviate the above-mentioned problem about the physical quality of the deposit is to use a specific organic additive in the EW method. More information about this type of additive can be found in, for example, Moats et al. (MS Moats, A. Luyima and W. Cui, copper electrowinning smoothing agent review, Part I: Overview, Minerals & Metallurgical Processing, Vol 33, pp 7-13, 2016). Organic additives such as guar gum, modified starch or polyacrylamide are necessary for promoting the plating of dense and smooth Cu deposits.
[0015] Working without the usual organic additives can lead to the formation of dendrites or nodules, especially at the edges of the cathode, which is undesirable. Their formation can even lead to short circuits in the EW cell.
[0016] Cifuentes et al. (L. Cifuentes, M. Mella, On the physical quality of copper electrodeposits obtained on mesh cathodes, Canadian Metallurgical Quarterly, Vol 45, no. 1, 9-16, 2006) studied the influence of process parameters on the Cu electrodeposition process in a reactive electrodialysis ("RED") cell in the absence of additives. At high Cu concentrations (9 g / L), deposits with nodules at the cathode edge were obtained, whereas at low Cu concentrations (3 g / L), deposits without nodules at the cathode edge and with uniform coverage were obtained. In contrast to conventional Cu-EW, cathode geometries that are not sheets or billets, such as copper pellets or copper mesh, are used. Furthermore, the cell geometry in the unconventional RED cell differs from the classical design in having two compartments separated by a membrane. In these cases, the chemical mass of the Cu deposit is determined in exactly the same way as in the conventional case, but the parameters of the physical mass need to be redefined. A new mass standard for Cu electrodeposition on copper mesh cathodes is proposed, which among other things addresses the co-deposition of arsenic present in the electrolyte. In this unconventional Cu-EW, the physical mass of the electrodeposit increases significantly with increasing cell current density, resulting in a significant increase in the physical mass for 290 A / m 2 The appropriate current density defines the "base case". For low current densities, such as 225A / m 2 , a deposit-free area was observed at the center of the cathode, and larger nodules were observed near the edges. 2 Under the circumstance, even larger areas with no deposit in the center and sharp nodules appear. Both are characterized as physically poor deposits with low coverage. When using a mesh cathode, Cifuentes generally does not mention how to achieve a sufficiently coherent copper deposit on the sheet or billet that does not decompose.
[0017] It is therefore an object of the present invention to form a coherent and uniform Cu deposit on a sheet or billet cathode at low current density in a Cu-EW process without the use of additives and without significant edge effects such as the formation of dendrites or nodules. This ensures that the risk of short circuits is minimized and that the deposit does not decompose from the cathode during the process, allowing easy harvesting.
[0018] Thus, a first embodiment describes a method for electrolytically depositing Cu onto a cathode starting sheet from an acidic aqueous solution containing one or more of Ni and Co and Cu, the method comprising the steps of:
[0019] -Provide copper electrowinning baths;
[0020] - electrolytic deposition of Cu from an aqueous sulfuric acid solution at a temperature of 50°C to 70°C, wherein the concentration of sulfuric acid is from 20 g / L to 100 g / L, wherein the concentration of Cu is at least 2 g / L and at most 15 g / L, and wherein the acidic aqueous solution contains no organic additives;
[0021] - applying means for stirring the electrolyte; and,
[0022] -Apply 100A / m 2 Up to 210A / m 2 The current density,
[0023] A Cu deposit is thus obtained on the cathode starting sheet.
[0024] Electrowinning is the electrodeposition of a metal that has been placed in solution via a process commonly known as leaching, done in a separate operation.
[0025] To achieve uniform Cu deposition in a standard EW cell with parallel electrodes in the absence of additives, the Cu-EW process was performed at low current density and low Cu concentration.
[0026] However, the Cu concentration cannot be too low, otherwise no coherent deposits are formed. This requires a minimum Cu concentration of about 2 g / L. On the other hand, a maximum Cu concentration of about 15 g / L should not be exceeded, because otherwise deposits with significant edge effects will be formed.
[0027] Under selected conditions, higher than 225A / m 2 Current densities below 100 A / m do not work as these lead to the formation of incoherent, highly porous deposits that easily decompose. 2 The current density of 2.5 Å leads to a too low capacity of Cu EW devices, which becomes economically unfeasible.
[0028] By "organic additives" is meant a family of products such as polysaccharides and oligosaccharides (e.g. guar gum and modified starches), (poly)peptides (e.g. gelatin), poly(meth)acrylic acid, poly(meth)acrylates and poly(meth)acrylate esters, polyethers, fluoropolymers, polyacrylamides, alkyl sulfonates and other organic sulfur and organic nitrogen compounds, including their degradation products. In certain flowsheets, the use of additives is very problematic, if not impossible, because these additives can interfere with subsequent steps such as hydrolysis, solvent extraction ("SX") or crystallization. It is also difficult to selectively remove such additives from the electrolyte prior to downstream processing. As a result, these additives often end up in the final product, which is undesirable. The same is true for their degradation products.
[0029] A second embodiment describes a process wherein the cathode starting sheet is a copper starting sheet or a stainless steel or titanium blank.
[0030] "Cathode starter sheets" are used in electrolytic deposition cells to deposit metals such as copper on flat surfaces. Such cathode starter sheets are usually in the form of thin copper starter sheets or billets made of stainless steel or titanium.
[0031] Cu deposited on copper starting sheets can be harvested and collected directly for further processing. Copper deposited on stainless steel or titanium billets is usually peeled (lifted) from the billet and then collected. In both cases, it is important that the Cu deposit is coherent and does not decompose, which would interfere with proper and quantitative collection of the metal.
[0032] In another embodiment, the current density is less than 200 A / m 2 , more preferably less than 150A / m 2 , even more preferably 140A / m 2 or lower.
[0033] Preferably below 150A / m 2 Or even 140A / m 2 The present invention is preferably operated at a current density of 1000 Å or lower to ensure a consistent and uniform Cu deposition under the process conditions of the present invention.
[0034] In another embodiment, the means for agitation include sparging with air or nitrogen, mechanical or ultrasonic agitation, or forced circulation.
[0035] "Means for stirring" is intended to mean the broadest possible means. Air sparging is often used, but air can be replaced by nitrogen or any other non-reactive gas, since the type of gas is not as important as the effect it produces when flushing through the electrolytic solution. Gases that react with copper or any other compound of the solution should obviously be avoided in the EW process.
[0036] Alternatively, stirring can also be achieved with ultrasonic or mechanical stirring or forced circulation, for example by optimized electrolyte injection, which causes vortexing and mixing of the electrolyte solution. Examples of "forced circulation" can be found in Cooper et al. (WC Cooper, Journal of Applied Electrochemistry, No. 15, pp. 789-805, 1985). Another option is periodic current reversal (PCR). Air injection is a preferred means for stirring.
[0037] In another embodiment, the copper electrowinning cell is a parallel plate cell. This cell type includes a rectangular cell containing flat anodes and cathodes, which are alternately placed in the cell. Flat plates are generally beneficial for copper recovery.
[0038] In another embodiment, H2SO4 has a preferred concentration of 40 g / L to 80 g / L.
[0039] Sulfuric acid is the preferred choice as it is most commonly used in leaching operations and is most commonly used in Cu-EW.
[0040] Compared to other Cu-EW processes that typically apply fairly acidic conditions (e.g., 180 g / L to 400 g / L H2SO4), the present invention works at significantly milder conditions (20 g / L to 100 g / L H2SO4), preferably 40 g / L to 80 g / L. This allows processing of leach solutions with mild acidity without the need for further acidification. It is also advantageous when a Cu-depleted process solution must be neutralized.
[0041] Industrial leach solutions recycled from cells typically have a concentration of 1 g / l acid to 20 g / l acid. This will typically result in an acid concentration of 40 g / L to 80 g / L in the EW process of the present invention, depending on the amount of Cu removed by electrowinning, as acid is generated as a result of the process.
[0042] In another embodiment, the acidic aqueous solution containing one or more of Ni and Co and Cu is obtained by leaching raw materials including lithium-ion batteries or their waste.
[0043] Modern waste streams for battery recycling can be very complex. Leaching solutions originating from battery recycling typically contain appreciable amounts of copper as well as nickel and / or cobalt. Therefore, the present method is particularly advantageous for processing such leach solutions.
[0044] In another embodiment, the aqueous sulfuric acid solution has a Ni concentration of at least 20 g / L.
[0045] In another embodiment, the aqueous sulfuric acid solution has a Co concentration of at least 5 g / L.
[0046] Typical leach solutions from battery recycling have a Ni concentration of at least 20 g / L and a Co concentration of at least 5 g / L. Such concentrations make them a valuable source of recovered metals.
[0047] In another embodiment, the acidic aqueous solution containing one or more of Ni and Co and Cu is free of arsenic. Co-deposition of As along with Cu is a recurring problem for streams containing both, resulting in reduced chemical quality of the Cu deposit. Li-ion batteries and their waste are generally free of arsenic.
[0048] When performing Cu-EW, the following three main deposit types have been observed and characterized. In the following examples, the Cu deposits obtained will be classified accordingly.
[0049] Type-1: The deposit is coherent and dense (low porosity) showing very limited formation of nodules or dendrites at the edges. Cu is deposited uniformly on the cathode surface.
[0050] Type-2: The deposit is coherent and dense but shows obvious nodule or dendrite formation at the edges. Hence, Cu is deposited unevenly on the cathode surface.
[0051] Type-3: The deposit is porous and incoherent. It has poor adhesion to the cathode and can be easily decomposed.
[0052] The following examples illustrate the invention.
[0053] Examples 1 to 3
[0054] Examples 1 to 3 were carried out as a batch process.
[0055] The Cu-EW beaker cell tests were conducted in a 2.8 L beaker cell connected to a circulation tank containing 50 L of electrolyte. A flow rate of 4.2 L / h and a temperature of 60° C. were selected. A synthetic electrolyte having the composition shown in Table 1 was used (Cu and H2SO4 not shown).
[0056] In the beaker cell, place an anode (PbCaSn, 9 × 2 cm 2 ) and cathode (Cu starting piece, 14 × 10 cm 2 ). The cathode current density was set to 140 A / m 2 , and the experiment was run and lasted for 7 days.
[0057] In such processes, Cu is removed from the electrolyte and deposited on the cathode, producing H2SO4.
[0058] This resulted in a decrease in Cu concentration of about 7 g / L and an increase in H2SO4 concentration of about 10 g / L. The initial and final Cu and H2SO4 concentrations are shown in Table 2.
[0059] Table 1 - Synthetic electrolyte composition
[0060]
[0061] Table 2 - Cu-EW beaker cell experiments using synthetic electrolytes
[0062]
[0063] The following conclusions can be drawn from these examples.
[0064] Comparative Example 2: The final Cu concentration was too high (35 g / L), thus resulting in Type-2 deposition.
[0065] Comparative Example 3: The final Cu concentration was too low (1 g / L), thus resulting in Type-3 deposition.
[0066] Testing in large batteries
[0067] Examples 4 to 12 were carried out as a continuous process.
[0068] Large-scale Cu-EW tests were conducted in a 13L cell connected to a 100L circulation tank. The electrolyte was circulated at 20L / h and heated to the desired temperature (40°C, 60°C, respectively) using an oil bath. In the cell, there were two anodes (PbCaSn, 89 × 7cm 2 ) and a cathode (Cu starting sheet, 94 × 8.5 cm 2 ). During the experiment, Cu was removed from the electrolyte and deposited on the cathode, while H2SO4 was produced. In order to keep the Cu and H2SO4 concentrations constant during the experiment (according to Table 3), the electrolyte in the circulation tank was supplied with an electrolyte with a high Cu concentration (40 g / L to 45 g / L) and a low H2SO4 concentration (2 g / L to 3 g / L). The composition of the electrolyte is shown in Table 1. Air sparging was applied below the cathode.
[0069] Table 3 - Overview of experiments in large-scale cells
[0070]
[0071] The following conclusions can be drawn from these examples.
[0072] Comparative Example 5: The Cu concentration was too high (20 g / L), which resulted in type-2 deposition.
[0073] Comparative Example 6: Current density is too high (225A / m 2 ), which results in type-3 deposition.
[0074] Comparative Example 8: The temperature was too low (40° C.), which resulted in type-3 deposition.
[0075] Comparative Example 10: No spraying was applied, which resulted in a Type-3 deposition.
[0076] Comparative Example 11: Use of organic additives at high Cu concentration resulted in Type-1 deposition.
[0077] Comparative Example 12: Use of organic additives at low Cu concentration resulted in Type-3 deposition.
Claims
1. A method for electrolytically depositing Cu onto a cathode starting sheet from an aqueous sulfuric acid solution containing one or more of Ni and Co and Cu, the method comprising the steps of: -Provide copper electrowinning baths; - electrolytic deposition of Cu from an aqueous sulfuric acid solution at a temperature of 50°C to 70°C, wherein the concentration of sulfuric acid is from 20 g / L to 100 g / L, wherein the concentration of Cu is at least 2 g / L and at most 15 g / L, and wherein the acidic aqueous solution contains no organic additives; - applying means for stirring the electrolyte; and, -Apply 100A / m 2 Up to 210A / m 2 The current density, Thereby obtaining a Cu deposit on the cathode starting sheet; The sulfuric acid aqueous solution containing one or more of Ni and Co and Cu is obtained by leaching raw materials including Li-ion batteries or their waste.
2. The method according to claim 1, wherein the cathode starting sheet is a copper starting sheet or a stainless steel or titanium billet.
3. The method according to claim 1 or 2, wherein the current density is less than 200 A / m 2 , more preferably less than 150A / m 2 , even more preferably 140A / m 2 or lower.
4. A process according to any one of claims 1 to 3, wherein the means for agitation comprises sparging with air or nitrogen, mechanical or ultrasonic agitation or forced circulation.
5. A method according to any one of claims 1 to 4, wherein the copper electrowinning cell is a parallel plate cell.
6. The method according to claims 1 to 5, wherein the aqueous sulfuric acid solution has a Ni concentration of at least 20 g / L.
7. The method according to claims 1 to 5, wherein the aqueous sulfuric acid solution has a Co concentration of at least 5 g / L.
Citation Information
Patent Citations
Method for treating lithium ion battery waste
WO2019102765A1
Battery recycling by treatment of the leach with metallic nickel
WO2019121086A1